Analysis the Development of Social Media for Marketing: Systematic Literature Review - Yofiendi Indah Indainanto (Persepsi: Communication Journal, 2023)
Social media platforms are increasingly being used for marketing activities. Many companies have integrated them into their marketing strategies, which can drive actual and potential interactions through engagement. The emergence of social media as a link between different aspects of marketing has driven innovation and use in influencing decisions. Over the past three years, research interest in social media as a marketing tool has led to increased innovation and interaction. The purpose of this study was to determine the development of social media as a marketing tool. The method used is a systematic literature review through bibliometric analysis. The results show that social media has a significant impact on changing marketing. The great potential of social media is used as a medium for both companies and buyers. The main concern tends to be the effect of use, introducing products and building product knowledge for buyers. Social media is used as a medium to manage knowledge information for consumers from in-depth searches, conversations and purchase decisions. Behavioural and knowledge-based perspectives are used by researchers to examine the role and impact of social media. The interconnectedness of social media makes it important to develop digital marketing optimisation strategies.